Arid Coastal Carbonates and the Phanerozoic Record of Carbonate Chemistry. Issue 3 (6th August 2021) - Smith, B. P.; Cantine, M. D.; Bergmann, K. D.; Ramos, E. J.; Martindale, R. C.; Kerans, C.
Abstract: Ocean chemistry and carbonate sedimentation link Earth's climate, carbon cycle, and marine pH. The carbonate system in seawater is complex and there are large uncertainties in key parameters in deep time. Here, we link sedimentary textures formed in arid coastal environments and preserved in the rock record to past seawater carbonate chemistry. Prior to the mid‐Mesozoic, tepee structures and pisoids – features associated with peritidal environments – co‐vary with available shelf area during cycles of supercontinent formation and rifting. In contrast, tepees and pisoids are consistently scarce after the mid‐Mesozoic, which coincides with a radiation in pelagic calcifiers as well as the breakup of Pangea. Numerical models suggest that the global and temporal abundances of tepee structures and pisoids are correlated with secular shifts in seawater chemistry, and that trends likely reflect the underlying influence of tectonics and biotic innovation on marine alkalinity and the saturation states of carbonate minerals. As independent sedimentary proxies, tepees and pisoids serve as benchmarks for global carbon cycle models and provide a new proxy record of seawater chemistry that can help discern links among tectonics, biotic innovation, and seawater chemistry. Plain Language Summary: Sedimentary rocks tell us that Earth's oceans and atmosphere have changed through time. Changes in the carbon cycle – the movement of carbon between Earth's interior and surface, including its distribution within oceans, atmospheres, and biological material – is important because it connects Earth's climate, oceans, life, and surface environments. Here, we present a new method for tracking carbon cycle changes based on textures in carbonate rocks. Certain textures were more common in hot, salty coastal areas up until 170 million years ago. Changes in the sedimentary record coincide with the appearance of tiny new organisms that build carbonate skeletons. Our data from non‐skeletal carbonates support the idea that this evolutionary event substantially changed ocean chemistry. We also outline how these sedimentary proxies might be used to test the co‐evolution of life and Earth's surface in deep time. Key Points: Carbonate facies in arid coastal environments track changes in carbonate mineral saturation state and alkalinity Facies trends show a major reorganization of ocean chemistry coinciding with the evolution of pelagic calcifiers in the mid‐Mesozoic Arid coastal deposits provide geologic evidence for changes in carbonate chemistry that can be applied in deep time